The ideologization of G.E. Lessing’s work in the period of the Polish People’s Republic on the example of theatre programs for the stage productions Minna von Barnhelm and Emilia Galotti - Podlasiak, Marek (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
The subject of the article is the issue of the ideologization of G.E. Lessing’s work in the period of the Polish People’s Republic on the example of theatre programs for Minna von Barnhelm and Emilia Galotti. The analysis of archival materials and press reviews showed that the process of ideologization of Lessing’s works, presented on Polish stages during the Polish People’s Republic, was visible pri-marily in theatre programs for staging the dramas by the classic German author. However, the material of the performances of Lessing’s plays defended itself against political appropriation by socialist cultural functionaries.